AKTIVITAS IMUNOSTIMULAN KOMBINASI EKSTRAK ETANOLIK UMBI KELADI TIKUS (Typhonium flagelliforme (Lodd.) Blume), HERBA MENIRAN (Phyllantus niruri Linn.), DAN DAUN SIRIH MERAH (Piper crocatum) TERHADAP PROLIFERASI LIMFOSIT PADA MENCIT Balb/c YANG DIINDUKSI VAKSIN HEPATITIS B - , NOVITA NUR DIARINI, Drh. Retno Murwanti, M.P., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Phyllantus niruri linn., Piper crocatum, and Typhonium flagelliforme (lodd.) Blume that have an immunostimulant activity. The focus of purpose for this research is to know the immunostimulant effect of combination those three extracts through the lymphocyte proliferation in mice that induced by Hepatitis B vaccine. Extract was carried out by maseration using 70% of ethanol. The comparation of ethanolic extract for using were 25:100:50 that intended for Piper crocatum, Typhonium flagelliforme (Lodd.) Blume, and Phyllantus niruri Linn. The testing animals were divided into 4 groups which were each group consisting of 5 mice that free selected randomly. Group I is control group, group II is the group that treated by 10 mg/kg of body mass dose, Group III is the group that treated by 50 mg/kg of body mass dose, group IV is the group that treated by 100 mg/kg of body mass dose. Those foru groups were treated by p.o during 7 days and to be continuedly vaccinated on 8th day. All groups were terminated for examination at 13th day.. The test of lymphocyte proliferation using MTT reduction. The optical density (OD) data of lymphocyte proliferation were analyzed statistically by ANOVA using 95% of confidence level. The results show that there are no significant difference in OD of limphocyte proliferation for each treatment. Based on those facts, prove that the combination of those three extracts were not change the lymphocyte proliferation. Keywords: Phyllantus niruri Linn., Piper crocatum, Typhonium flagelliforme (Lodd.) Blume, Proliferation, Lymphocyte